Meta-Analysis of Factors Affecting Compliance Behavior in Taking Iron Folate Supplements in Pregnant Women - Farida Nur Aisyiyah; Eltigeka Devi Apriliani (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Pregnant women can have a higher risk of iron and folic acid deficiency due to poor adherence to iron folate supplements. Factors that influence pregnant women during antenatal check-ups on adherence to taking iron folate supplements are getting counseling, having knowledge, attending antenatal care and diagnosing anemia. This study aims to analyze the factors that influence the behavior of adherence to taking iron folate supplements in pregnant women.Subjects and Method: This was a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2011 and 2021 using databases from PubMed, Google Scholar and ScienceDirect. Based on the database, there were 12 articles that met the inclusion criteria. The analysis was carried out using RevMan 5.3 software.Results: A total of 12 articles reviewed in the meta-analysis showed that there were 7 articles discussing pregnant women who received nutritional counseling had higher adherence behavior to taking iron folate supplements and were statistically significant (aOR= 2.39; 95% CI= 1.92 to 2.96; p <0.001), and there were 8 articles discussing pregnant women with anemia who had higher adherence to taking iron folate supplements and were statistically significant (aOR= 3.28; 95% CI= 1.56 to 6.87; p= 0.002).Conclusion: Nutrition counseling and anemia status can improve the behavior of adherence to taking iron folate supplements in pregnant women.Keywords: supplement, iron-folic acid, anemia, counselingCorrespondence:Farida Nur Aisyiyah. Klaten District Health Office. Jl. Pemuda Nomor No.313, Mlinjon, Tonggalan, Central Klaten, Central Java. Email: faridanur88@gmail.com. Mobile: +62 852-1493-3173.Journal of Health Promotion and Behavior, (2021), 06(04): 339-354DOI: https://doi.org/10.26911/thejhpb.2021.06.04.08